La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.